Polymorphism in pharmaceutical solids - Brittain, Harry G. (New York, 2008)
Presents a comprehensive examination of polymorphic behavior in pharmaceutical development-demonstrating with clear, practical examples how to navigate complicated crystal structures. Edited by the recipient of the American Association of Pharmaceutical Scientists' 1998 Research Achievement Award in Analysis and Pharmaceutical Quality
Keywords: PHARMACEUTICS